PERSON-ORGANIZATION FIT AND SPIRITUAL MOTIVATION IN EXPLAINING ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE - Arif Afendi; Syukur Fatah; Furqon Ahmad; mashilal mashilal (SEGMEN: Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is to test the effect of person-organization fit and spiritual motivation on organizational commitment and employee performance. The type of research used is quantitative research using the Structural Equation Model (SEM) method. The data in this study was primary data with 100 respondents from Walisongo State Islamic University Semarang. The results of this study show that there is a positive and significant effect of person-organization fit and spiritual motivation on organizational commitment. The effect of the organizational commitment to employee performance is positive and significant. while the effect of person-organization fit and spiritual motivation on employee performance is also positive and significant.